Beni patrimoniali e beni simbolici: l’album fotografico della Principessa Luisa Scotto Corsini - Cestelli Guidi, Benedetta (Rivista di studi di fotografia. Journal of Studies in Photography, 2016)
This essay analyzes an album assembled by Roman Princess Luisa Scotto Corsini in the late 1880s and the use of a photographic object within a focused, yet coded narrative. While the album displays the Princess’ dynastic, socio-political, and exclusive private life, a section of prints recording each piece of furniture in the Corsini palace stands out for its apparent inconspicuousness. In fact, Luisa Scotto selected these deadpan records from an 1876 series by Filippo Belli to express her own grief after her Roman palace had to be sold to the Italian State in 1883. A multi-layered object, the photographic album thus entwines property and symbolic values to sublimate a sense of loss and displacement.